Pengukuran Beban Kerja Mental dan Fisik Operator Mesin Die Casting pada Shift Malam dengan Menggunakan Metode Nasa-TLX, CVL dan FTA - Alfin Kurnia Setiawan; Ayudyah Eka Apsari (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
MMP is a metal manufacturing company engaged in casting, forging, and machining processes with a three-shift work system, including night shifts that may increase mental and physical workload due to disruptions in workers’ biological rhythms. This study aims to analyze the mental and physical workload of die casting machine operators during the night shift and to propose improvement measures using the Fault Tree Analysis (FTA) method. The study involved 23 operators, with mental workload assessed using NASA-TLX and physical workload measured using CVL. The results indicate that mental workload falls into high to very high categories, with WWL values ranging from 46.6 to 97.3, where 12 operators experienced very high mental workload. The dominant contributing dimensions were effort, physical demand, and temporal demand. Meanwhile, physical workload ranged from 19.48% to 36.36% CVL, with most operators not experiencing fatigue. Although physical workload remains within acceptable limits, the high mental workload indicates the need for improvements. FTA analysis identified key contributing factors, including work methods, work systems, ergonomics, machine conditions, and the work environment. Proposed improvements include job rotation, improvements in work methods and task distribution, adjustments to the work system, enhanced machine maintenance, and ergonomics-based workplace improvements.